Using functional Transcranial Doppler Ultrasonography to assess language lateralization: Influence of task and difficulty level. - Bishop, D; Nye, A; Badcock, N (Routledge, 2012)
Language is lateralised to the left hemisphere in most people, but it is unclear whether the same degree and direction of lateralisation is found for all verbal tasks and whether laterality is affected by task difficulty. We used functional transcranial Doppler ultrasonography (fTCD) to assess the lateralisation of language processing in 27 young adults using three tasks: word generation (WG), auditory naming (AN), and picture story (PS). WG and AN are active tasks requiring behavioural responses whereas PS is a passive task that involves listening to an auditory story accompanied by pictures. We also examined the effect of task difficulty by a post hoc behavioural categorisation of trials in the WG task and a word frequency manipulation in the AN task. fTCD was used to measure task-dependent blood flow velocity changes in the left and right middle cerebral arteries. All of these tasks were significantly left lateralised: WG, 77% of individuals left, 5% right; AN, 72% left: 4% right; PS, 56% left: 0% right. There were significant positive relationships between WG and AN (r=0.56) as well as AN and PS (r=.76) but not WG and PS (r = −0.22). The task difficulty manipulation affected accuracy in both WG and AN tasks, as well as reaction time in the AN task, but did not significantly influence laterality indices in either task. It is concluded that verbal tasks are not interchangeable when assessing cerebral lateralisation, but that differences between tasks are not a consequence of task difficulty.